Dissecting endothelial cell heterogeneity with new tools - Jing Zhong; Rong-rong Gao; Xin Zhang; Jia-xin Yang; Yang Liu; Jinjin Ma; Qi Chen (Cell Regeneration)
Abstract The formation of a blood vessel network is crucial for organ development and regeneration. Over the past three decades, the central molecular mechanisms governing blood vessel growth have been extensively studied. Recent evidence indicates that vascular endothelial cells—the specialized cells lining the inner surface of blood vessels—exhibit significant heterogeneity to meet the specific needs of different organs. This review focuses on the current understanding of endothelial cell heterogeneity, which includes both intra-organ and inter-organ heterogeneity. Intra-organ heterogeneity encompasses arterio-venous and tip-stalk endothelial cell specialization, while inter-organ heterogeneity refers to organ-specific transcriptomic profiles and functions. Advances in single-cell RNA sequencing (scRNA-seq) have enabled the identification of new endothelial subpopulations and the comparison of gene expression patterns across different subsets of endothelial cells. Integrating scRNA-seq with other high-throughput sequencing technologies promises to deepen our understanding of endothelial cell heterogeneity at the epigenetic level and in a spatially resolved context. To further explore human endothelial cell heterogeneity, vascular organoids offer powerful tools for studying gene function in three-dimensional culture systems and for investigating endothelial-tissue interactions using human cells. Developing organ-specific vascular organoids presents unique opportunities to unravel inter-organ endothelial cell heterogeneity and its implications for human disease. Emerging technologies, such as scRNA-seq and vascular organoids, are poised to transform our understanding of endothelial cell heterogeneity and pave the way for innovative therapeutic strategies to address human vascular diseases. Graphical Abstract